Sarcophagidae (Diptera) of forensic importance in Colombia: taxonomic keys, notes on biology, and distribution - BUENAVENTURA-R., ELIANA; CAMACHO-C., GINNA; GARCÍA-G., ALEXANDER; WOLFF-E., MARTA (Revista Colombiana de Entomología, 2009)
An illustrated key to the identification of males from 16 genera of Sarcophagidae of forensic importance in Colombia is presented, as well as comments about their biology and distribution. The included genera were: Argoravinia, Blaesoxipha, Boettcheria, Dexosarcophaga, Engelimyia, Helicobia, Microcerella, Oxysarcodexia, Peckia, Ravinia, Sarcodexia, Sarcofahrtiopsis, Sarcophaga, Titanogrypa, Tricharaea and Oxyvinia. The latter is a new record for the country.